CRS and its impact on profitability : Developed and Developing Countries Comparative Study - Devi, Pushpa (My University, 2025)
Corporate Social Responsibility (CSR) is the cost of doing business. The corporations are expected to contribute to society and behave responsibly towards the environment for the damage they have caused. CSR has gained significance over the last decade. It comprises Environmental, Social, and Governance goals that should align with the Sustainable Development Goals (SDGs). This thesis examines the correlation between two variables, i.e. CSR and profitability in banks, to analyse changes in CSR in CSR-oriented banks. It further investigates whether this relationship acts differently as on the economic status of different nations. The study is carried out on the basis of six countries that were chosen to collect the data on the topic, i.e., the United States, United Kingdom, Japan, India, Pakistan, and Nigeria, to use the sample during 2010-2020 and utilises the mixed-method design that presupposes utilising the quantitative regression analysis and the qualitative institutional comparison. Return on Assets (ROA) and Return on Equity (ROE) are the performance indicators used to determine the profitability, and CSR spending and disclosure indices are the measures used to evaluate CSR engagement. The results indicate a strong positive correlation between CSR and profitability, which proves that socially responsible banking increases the efficiency of operations and the value of shareholders. In the developed economies, the relationship is stronger and is enabled by the presence of mature institutions, quality of regulation, and transparency, which enables the integration of strategic CSR. Conversely, CSR in emerging economies is inclined towards philanthropy or regulatory activities with poor or unequal financial outcomes. The fact that it brings together crisis variables is another indication that CSR can be used to strengthen the resilience of banks in the face of a financial crisis. The paper upholds Stakeholder and Legitimacy Theories, indicating that CSR brings about trust, legitimacy and long-run performance. In a practical context, it suggests that bank managers should see CSR as a strategic investment and not as an expenditure and that policymakers should facilitate systems that would promote true and transparent CSR. The study goes beyond the current literature by employing the institutional context to the CSR profitability nexus, which demonstrates CSR as the cause of sustainable profitability and risk management in the banking system of the world
Keywords: corporate responsibility; return; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance